Symbol Ritual and Dementia - Hide, Kerrie (Journal of religious gerontology, 2003)
This article draws on the experiences of prayer of people with dementia. After pointing to the profoundly symbolic nature of all human beings and presenting a theology of symbol and ritual expressive of the Christian tradition, it argues that symbol and ritual can enable people with dementia to express what is ultimately of most meaning in their lives. Carers sensitive and responsive to the inherently symbolic nature of people with dementia can nourish and enrich their relationship with the divine.